Improving working memory in children with low language abilities - Holmes, Joni; Butterfield, Sally; Cormack, Francesca; Loenhoud, Anita van; Ruggero, Leanne; Kashikar, Linda; Gathercole, Susan (Frontiers in Psychology, 2015)
This study investigated whether working memory training is effective in enhancing verbal memory in children with low language abilities (LLA). Cogmed Working Memory Training was completed by a community sample of children aged 8 to 11 years with LLA and a comparison group with matched nonverbal abilities and age-typical language performance. Short-term memory, working memory, language and IQ were assessed before and after training. Significant and equivalent post-training gains were found in visuo-spatial short-term memory in both groups. Exploratory analyses across the sample established that low verbal IQ scores were strongly and highly specifically associated with greater gains in verbal STM, and that children with higher verbal IQs made greater gains in visuo-spatial short-term memory following training.. This provides preliminary evidence that intensive working memory training may be effective for enhancing the weakest aspects of STM in children with low verbal abilities, and may also be of value in developing compensatory strategies.